CONCEPT AND CONCEPTUALIZATION: METHODOLOGY FOR THE STUDY OF CULTURE AND RELIGION - Konotop, Liudmyla (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The article is devoted to the philosophical understanding of the relationship between culture and religion, their interaction in the modern world. The methodology for studying the relationship between culture and religion presupposes clear definitions of conceptualization and concept. In modern Ukrainian religious studies, there are no methodological approaches to the study of religion, the features of its functioning in society. The main task of the article is to reveal the features of the relationship between culture and religion in their historical movement. Various stages of their relationship are revealed. The main research methods are: interdisciplinary, dialectical, historical, non-confessional. Research results are the basic value propositions about culture in its historical movement, as well as the variety of philosophical and religious searches at different stages of the formation of mankind, are revealed. Conceptualization is a process of intellectual coding of ideas that highlight the meaning of understanding culture in a particular language area. The concept is the result of individual and collective cognition. The concept includes, firstly, the meanings that belong to reality, and secondly, it opens up possibilities for the search and interpretation of these meanings. In this regard, it is impossible to provide the concept with any universal definition. A concept is perceived by another person if the idea contained in the concept correlates with the experience of a particular person. The discussion leads to the fact that the dynamics of the movement of culture is decisive for the development of society, while religion, to a certain extent, can have negative consequences. Conclusions. Any "modernization" of Christianity leads to the dominance of non-traditional religious currents and movements.